Identification of novel functional compounds from forest onion and its biological activities against breast cancer - Nurkolis, Fahrul; Kurniatanty, Isma; Wiyarta, Elvan; Permatasari, Happy Kurnia; Mayulu, Nelly; Taslim, Nurpudji Astuti; Tjandrawinata, Raymond Rubianto; Hardinsyah, Hardinsyah; Tallei, Trina Ekawati; Tsopmo, Apollinaire; Radu, Son; Hadinata, Edwin; et al. (Elsevier, 2024)
The discovery of new molecules from natural sources for the treatment of tumors such as breast cancers is of importance for the development of functional foods and to the pharmaceutical industry. A natural resource with potential activity against breast cancer is forest onion, Eleutherine bulbosa (Mill.) Urb., but the identity of its active constituents and their mechanisms of action remain unexplored. Therefore, this study focuses on metabolite profiling, in silico or pharmacoinformatic activity and mechanisms, as well as advanced validation on in vitro cell lines. Ten compounds identified in E. bulbosa bulb ethanolic extract (EBE) showed cancer receptor and radical inhibitory activity via network pharmacology and molecular docking simulation. The most promising compound was avenasterol binding PARP-1, HER2, iNOS receptors with values of −11.26, −8.34, and −9.17 μg/mL, respectively. EBE and avenasterol had a smaller EC50 value, or higher potency, than the control antioxidant Trolox in radical scavenging tests with ABTS and DPPH. In line with the in silico study, EBE and avenasterol showed antiproliferative activity against human breast cancer MCF-7 with LD50 217.8 μg/mL, with relatively low cytotoxicity to normal MCF-10A cells (LD50 > 1000 μg/mL). The antiproliferative mechanism of EBE on MCF-7 was associated with downregulation of TGF-β, HER2, PI3K, and AKT which are known tumor activators. Significant (p < 0.05) upregulation of tumor suppressor gene miR-29a-3p in MCF-7 was observed after treatment with EBE in a dose-dependent manner. © 2024 The Authors